2021
DOI: 10.2147/ijn.s306186
|View full text |Cite
|
Sign up to set email alerts
|

Using Green Biosynthesized Lycopene-Coated Selenium Nanoparticles to Rescue Renal Damage in Glycerol-Induced Acute Kidney Injury in Rats

Abstract: Purpose Selenium nanoparticles (SeNPs) have recently gained much attention in nanomedicine applications owing to their unique biological properties. Biosynthesis of SeNPs using nutraceuticals as lycopene (LYC) maximizes their stability and bioactivities. In this context, this study aimed to elucidate the renoprotective activity of SeNPs coated with LYC (LYC-SeNPs) in the acute kidney injury (AKI) model. Methods Rats were divided into six groups: control, AKI (glycerol-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 58 publications
5
29
0
Order By: Relevance
“…The prepared PDGs-SeNPs calculated crystalline size is < 134 nm using Scherrer’s equation. This amorphous character is in agreement with the earlier studies carried out with lycopene 48 and different bacterial sp. 49 Moreover, TEM is employed to analyze the shape of the PDGs-SeNPs biosynthesized with PDGs.…”
Section: Resultssupporting
confidence: 93%
“…The prepared PDGs-SeNPs calculated crystalline size is < 134 nm using Scherrer’s equation. This amorphous character is in agreement with the earlier studies carried out with lycopene 48 and different bacterial sp. 49 Moreover, TEM is employed to analyze the shape of the PDGs-SeNPs biosynthesized with PDGs.…”
Section: Resultssupporting
confidence: 93%
“…The XRD results revealed that the myco-synthesized SeNPs are rather more amorphous than crystalline. This amorphous nature is consistent with previous research with lycopene [ 61 ], Pseudomonas stutzeri [ 62 ], and Withania somnifera [ 63 ]. FTIR analysis revealed the interaction between P. chrysogenum metabolites and SeNPs.…”
Section: Discussionsupporting
confidence: 92%
“…NGAL is a recent marker that have been used to aid diagnosis and it has been shown to be more sensitive and speci c than classical markers such as creatinine and blood urea nitrogen (BUN). However, new biomarkers such as NGAL does not only serve as indicators of glomerular damage, but also tubular impairment(Naja et al 2021;Al-Brakati et al 2021). In this study, the kidneys of Pb treated birds showed high expression of NGAL when compared with birds co-treated with naringin.…”
mentioning
confidence: 52%
“…Neutrophil gelatinase-associated lipocalin (NGAL) is a member of the lipocalin superfamily of proteins that has been extensively studied in acute kidney injury. NGAL is one of the most robustly expressed proteins in the kidney following ischemic or nephrotoxic injury in animals and human(Jia et al 2021;Kovacevic et al 2021;Naja et al 2021;Al- Brakati et al 2021). NGAL is a recent marker that have been used to aid diagnosis and it has been shown to be more sensitive and speci c than classical markers such as creatinine and blood urea nitrogen (BUN).…”
mentioning
confidence: 99%